Immunohistochemical Characterization of Spontaneous Sertoli Cell Clusters in the Seminiferous Tubules of C57BL/6J Mice. (July 2015) - Anagawa-Nakamura, Akiko; Kakimoto, Kochi; Miyajima, Katsuhiro; Yasui, Yuzo; Kemmochi, Yusuke; Toyoda, Kaoru; Taniai, Eriko; Takahashi, Akemi; Shoda, Toshiyuki
Cell clusters were observed in the seminiferous tubules of C57BL/6J mice as a spontaneous lesion in a 2-week toxicity study, and they were demonstrated to be basically composed of Sertoli cells by immunohistochemistry for claudin-11 and GATA-4 (GATA-binding protein 4), which are both Sertoli cell markers. The clusters were composed of about 5 to 50 cells, which had eosinophilic and occasionally vacuolated cytoplasm with an unclear cell boundary. The cell clusters involved some sperm. No mitotic figures were observed and no immunoreactivity for proliferating cell nuclear antigen (PCNA) was detected in the clusters. In most cases, the cell clusters were observed in seminiferous tubules that also showed degenerative changes. In rare instances, cell aggregates immunohistochemically positive for claudin-11 were observed in the lumen of the epididymis, suggesting that some of the Sertoli cell clusters were sloughed off from the seminiferous epithelium into the epididymal ducts. To our knowledge, this is the first report of Sertoli cell clusters in any animal species except for transgenic or surgically altered animals.